APRENDIZAJE RECIPROCO Y EL CUIDADO DEL PLANETA - SARASUA, CARLOS M.; PAULOVSKY, ELSA E.; MELNIK, GRACIELA T.; ALMIRÓN, MARÍA E.; WALL, NELIDA L.; BULFFE, RITA; VERÓNICA, SPINOZZI C. (Salão do Conhecimento, 2013)
Resumo